Influence of soil texture on the process of subsurface drainage in saturated-unsaturated zones - Li, Yufang; Li, Mingsi; Liu, Hongguang; Qin, Wenbao (International Journal of Agricultural and Biological Engineering, 2021)
This study addressed the problem of low drainage efficiency or even no drainage in subsurface drainage systems buried in saturated-unsaturated zones above the water table. An indoor experiment on infiltration under ponded conditions in a homogeneous soil column was performed to study the effects of soil texture on the soil wetting front morphology, soil infiltration rate, drainage efficiency of the subsurface drainage pipe, vertical distribution of soil water content and salinity along the soil column. The results showed that the drainage process of subsurface drainage pipes above the water table was quite different from that of subsurface drainage pipes below the water table. When a subsurface drainage pipe was located in sandy soil, the migration of soil water toward the bottom of the drainage pipe was significant, and the water could not be discharged into the pipe. When the drainage pipe was located in loamy clay, the movement of soil water towards the bottom of the pipe was retarded, and the water could be discharged into the pipe. During the drainage process, the drainage of the pipe can produce nonequilibrium flow in the soil, and the continuity of the nonequilibrium flow can be affected by the hydraulic conductivity of the soil above the pipe, which can result in discontinuous drainage and low drainage efficiency. The water holding capacity, permeability and aeration of soil are important factors that affect the drainage under unsaturated conditions. Eliminating the hysteresis effect and capillary barrier around the drainage pipe and adjusting water holding capacity, the permeability and aeration of soil structure through a new subsurface drainage structure may enhance the drainage efficiency of subsurface drainage pipes in saturated-unsaturated zones.Keywords: saturated-unsaturated zone, soil texture, subsurface, drainage pipe, groundwater levelDOI: 10.25165/j.ijabe.20211401.5699Citation: Li Y F, Li M S, Liu H G, Qin W B. Influence of soil texture on the process of subsurface drainage in saturated-unsaturated zones. Int J Agric & Biol Eng, 2021; 14(1): 82–89.